Terminating Cancer by Blocking VISTA as a Novel Immunotherapy: Hasta la vista, baby - Yum, Ji-Eun Irene; Hong, Young-Kwon (Frontiers in Oncology, 2021)
VISTA is an up-and-coming immune checkpoint molecule that has the potential to become the target of new cancer immunotherapy treatments. Immune cells in the tumor microenvironment can largely influence the progression of cancer through inhibitory and stimulatory pathways. Indeed, VISTA has been found to be expressed on a multitude of immune cells, including T cells, myeloid-derived suppressor cells, tumor-associated macrophages, and dendritic cells. VISTA has predominantly been shown to act in an immune-suppressing manner that enables cancer progression. This review will delve into results from pre-clinical murine studies of anti-VISTA monoclonal antibody treatments, bring together recent studies that detect VISTA expression on immune cells from patient tumors of various cancers, and discuss ongoing clinical trials involving VISTA.